Is mean platelet volume a new activity criteria in Behçet's disease?. Issue 7 (October 2015) - Uzkeser, Hulya; Haliloglu, Sema; Cayir, Yasemin; Bilen, Nurhan; Karaaslan, Yasar; Kosar, Ali; Carlioglu, Ayse
Abstract : The aim of this study was to assess mean platelet volume (MPV) and its relationship with disease activity in patients with Behçet's disease. Thirty-six patients with an age of 38.9 ± 11 (mean ± SD) years and 40 controls aged 36.5 ± 12 (mean ± SD) years were enrolled the study. Demographic data, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), MPV, clinical findings such as oral aphthae, genital aphthae, erythema nodosum, acne, central nervous system involvement, uveitis, arthritis and arthralgia were all recorded. The MPV value in patients with Behçet's disease was 8.06 ± 1.0 (mean ± SD) and the MPV value of the control participants was 7.45 ± 0.6 (mean ± SD). MPV was statistically higher in patients with Behçet's disease than in the controls ( P  = 0.003). There were also significant differences between patients and controls according to ESR and CRP values ( P  < 0.001 and P  = 0.001, respectively). MPV was positively correlated with arthralgia ( P  < 0.001, r  = 0.438), arthritis ( P  = 0.008, r  = 0.307), erythema nodosum ( P  = 0.002, r  = 0.354), central nervous system involvement ( P  = 0.002, r  = 0.357), acne ( P  = 0.008, r  = 0.312), genital aphthae ( P  < 0.001, r  = 0.401) and oral aphthae ( P  = 0.001 r  = 0.377). MPV can be easily obtained from the patients. It was a cheap and practical method. In the future, MPV may be used as a new marker to detect the activation of BD.